Perbandingan Model Problem Based Learning dan Model Inquiry Terhadap Hasil Belajar IPA SD - Een Unaenah; Ima Muawiyah (Jurusan Pendidikan Guru Madrasah Ibtidaiyah, 2019)
This study aims to determine whether there is a difference between the problem based learning model and the inquiry model on science learning outcomes. This research method is quantitative research. The sample of this study was taken from 2 classes, experimental class 1 and experimental class 2, with 30 students each. In each research class, two tests were conducted, namely pretest and posttest. The formulation of the problem in this study are: 1) Students are still difficult in learning science subjects, 2) Learning models used are less innovative, 3) Motivation of students in participating in science learning is still lacking so students are less motivated and reinforced when the learning process takes place, 4) Monotonous learning, less variative, 5) Lack of student interest in learning. The results revealed that science learning outcomes taught using the problem based learning model with inquiry model differed. This can be seen from the average value of the posttest results of science learning outcomes taught using the problem based learning model is 68.3 and the average score of the posttest learning outcomes in the inquiry model is 76.8. Based on the hypothesis test using the t- test obtained tcount (3.801)> ttable (1.997), the research hypothesis Ho is rejected, meaning that there are differences in learning outcomes of students who are given the Problem Based Learning model with students who are treated by the Inqury model. Keywords: Inquiry, Problem Based Learning, Science